Standardization of protocol for in vitro tuberization in potato (Solanum tuberosum) cultivar Kufri Sindhuri - SHARMA, MANMOHAN; SHARMA, MAMTA; SALGOTRA, ROMESH KUMAR; SHARMA, MRIDHU; SINGH, ANJANI K (The Indian Journal of Agricultural Sciences, 2023)
Potato (Solanum tuberosum L.) is an economically important dicotyledonous and tuber crop which is ranked as the fourth most cultivated food crop after wheat, rice and maize. Asexual propagation of potato is done through tubers which are prone to large number of fungal and viral diseases. Microtubers produced through tissue culture serve as an essential component for production of disease-free quality potato seed. The present study was carried out during 2018 and 2019 at School of Biotechnology, Sher-e-Kashmir University of Agriculture Science and Technology of Jammu, Jammu to standardize in vitro microtuber production protocol in potato variety Kufri Sindhuri using different explants. Nodal segments were the most suitable explants for culture establishment which resulted in maximum survival with least contamination and mortality. Murashige and Skoog medium supplemented with BAP (1.5 mg/litre) and NAA (0.1 mg/litre) resulted in 100% shoot regeneration with 3.75 shoots per explant. Vigorous shoot proliferation was achieved by fortification of calcium pentothenate (2 mg/litre) and gibberellic acid (0.25 mg/litre) in establishment medium. Pre-tuberization was done by incubating cultures for 28 days in liquid multiplication medium supplemented with NAA (0.5 mg/litre). Maximum microtubers (24) per culture flask were obtained in 10 days when tuberization medium was fortified with 80 g/litre of sucrose while maximum diameter of 0.9 cm was recorded in the presence of growth retardant chlorocholine chloride (500 mg/litre). Complete darkness was an essential factor for microtuber induction. The harvested microtubers (G0) were stored at 4°C after treating them with fungicides.